Inventory Control of Raw Material Requirement in NPK Fertilizer Production Using the Min-Max Method at PT ABC - Putri, Shelany Andhika; Tranggono (Journal Knowledge Industrial Engineering (JKIE), 2025)
PT ABC, a company in the fertilizer and chemical industry. One of the fertilizer products produced is NPK fertilizer, which is highly beneficial for enhancing the quantity and quality of agricultural products, making it a crucial input for farmers. To ensure efficient production and customer satisfaction, it is necessary to calculate inventory control for raw materials for products. In this study, the forecasting method that has the lowest error value is the double exponential smoothing method with MAPE 12% and MAD 17311. Where the forecasting results for each raw material will be used to calculate raw material requirements with the min-max method. The minimum stock levels for Ammonia (NH3) are 3,981 tons; Sulfuric Acid (SA) 8,391 tons; Phosporic Acid (PA) 6,037 tons; DAP 16,578 tons; KCL 64,859 tons; ZA 9,485 tons; and Urea 114 tons. The maximum stock levels for Ammonia (NH3) are 5,292 tons; Sulfuric Acid (SA) 11,147 tons; Phosporic Acid (PA) 8,243 tons; DAP 8,243 tons; KCL 109,823 tons; ZA 12,312 tons; and Urea 169 tons.